Techno-economic assessment of a solar-based novel power generation system formed from a helium Brayton cycle and an organic Rankine flash cycle - Sharma, Achintya; Shukla, Anoop Kumar; Singh, Onkar; Sharma, Meeta (Frontiers in Energy Research, 2024)
The essential element for human existence is energy. However, conventional energy sources are steadily running out. Therefore, it is demanding to create an energy-efficient renewable power generation system. Therefore, in the present work, the organic Rankine flash cycle (ORFC) was implemented in the conventional solar power tower (SPT)-helium Brayton cycle (HBC) to generate extra power, enhancing efficiency. The proposed SPT-based power generation system (SPT-HBC-ORFC) performance was analysed based on thermodynamic and economic aspects using computational technique through engineering equation solver software. The results revealed that the proposed power plant’s energy efficiency, exergy efficiency, power output, and total cost rate were found to be 33.68% and 33.70%, 33.69%, and 15.47%, respectively, higher than that of the conventional SPT-HBC system, at given conditions. With a 39% part of all exergy destruction, heliostats are the source of the greatest exergy destruction. Parametric analysis reveals that solar subsection parameters affected more the performance of the proposed power plant. Comparisons with previous studies show that the present power generation system is highly efficient than that of the SPT-based supercritical CO2 Brayton and Rankine cycles.